Um estudo comparativo dos níveis de satisfação e o grau de importância da qualidade de vida no trabalho em uma Instituição Pública - Rodrigues, Maria Reijane de Morais Santos (2015)
Nowadays the world stage is characterized by constant changes that impose organizations continuous changes in their management methods, which require professionals even more able to meet the market demand. However, at the same time they become more productive and competitive, more physical and psychological illnesses are found among their professionals. In this context, there appears the need of investment on Quality of Work Life (QWL) to minimize and eradicate such negative effects. Several concepts are assigned to QWL, but because it is a complex issue there is no consensus about its definition. Evaluation models of QWL arise mainly from the 70’s and stand out as reference even today. This study, of quantitative character, aims to conduct a comparative analysis between the degrees of satisfaction and the degrees of importance attributed to Quality of Work Life (QWL) from the perspective of servers, contractors and managers in a federal public institution. As data tool collection, it is used a questionnaire based on the Walton Model, that identifies eight factors related to QWL. For the interpretations and analysis of the results, the classic statistic methods are applied: exploratory data analysis and statistical inference, in particular the nonparametric hypothesis tests, the Wilcoxon test and the Mann-Whitney test. The results reveal that, for every factor, the servers’ degree of satisfaction is in negative discordance in relation to the degree of importance. It is concluded, therefore, that these factors show a deficiency in relation to QWL, and that this deficit results from an imbalance between the real servers’ necessities given the importance they attribute to QWL and the inability of the researched institution to meet them.